1990
DOI: 10.1159/000185808
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Immunity in Adult Primary Glomerulonephritis

Abstract: Salivary components (proteins, albumin, IgA1, IgA2, IgG, IgM, β2-microglobulin, neopterin and peroxidase) were investigated in 3 adult types of primary glomerulonephritis (PGN): IgA mesangial glomerulonephritis (IgAGN; n = 14); idiopathic membranous glomerulonephritis (n = 8); idiopathic nephrotic syndrome (INS; n = 14), and a control group (n = 11). Salivary IgAl levels were significantly increased in all these PGN whereas salivary IgA2 levels were only higher than controls in INS. Albumin and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…␤2M is a product of a variety of activated lymphoid cells. ␤2M has also been detected in human saliva, and significantly higher levels were found in saliva from patients with juvenile periodontitis (1), adult primary glomerulonephritis (28), and primary Sjögren's syndrome (20). There are no reports on ␤2M measurements in the saliva of HIV-infected individuals.…”
mentioning
confidence: 99%
“…␤2M is a product of a variety of activated lymphoid cells. ␤2M has also been detected in human saliva, and significantly higher levels were found in saliva from patients with juvenile periodontitis (1), adult primary glomerulonephritis (28), and primary Sjögren's syndrome (20). There are no reports on ␤2M measurements in the saliva of HIV-infected individuals.…”
mentioning
confidence: 99%
“…The fact that deposited IgA in the glomerular mesangium in IgAN is predominantly polymeric IgA1, which is usually derived mainly from the mucosal immune system, suggests that the pathogenesis of this disease is related to abnormality of mucosal immunity [10]. In fact, many studies have suggested the involvement of mucosa in the immunological abnormalities in IgAN [11–16]. In the mucosal immune system, a unique type of T cell bearing γδ TCR ( γδ T cell) is distributed more abundantly than are αβ TCR‐positive T cells ( αβ T cells), which are more common in peripheral blood and other lymphoid organs.…”
Section: Introductionmentioning
confidence: 99%